THE EFFECT OF MARKET ORIENTATION ON GOFOOD PARTNER MARKETING PERFORMANCE IN SURABAYA - Suhelmi, Suhelmi; Susilowati, Luky; Zumrotul, Zumrotul (Jurnal Ekonomi Balance, 2021)
Today's digital start-ups have succeeded in creating a new trend and can solve problems in society. One that is attracting attention today is Gojek. Not only does it provide benefits from the consumer side, but Gojek can also provide benefits from the business side, one of which is by joining as a GoFood business partner or commonly called a "GoFood Partner". This study aims to determine the effect of market orientation on the marketing performance of Gofood Partners in Surabaya. This study involved 70 respondents who are owners or managers and customers of Gofood in the city of Surabaya. By using the Purposive sampling method, data collection was carried out by distributing questionnaires. The analytical technique used in this research is using the component-based SEM method using PLS. The results found indicate that Market Orientation has a positive effect on Marketing Performance. The better the market orientation carried out by gofood partners, the marketing performance will also increase.